An alternative model for the early peopling of Southern South America revealed by analyses of three mitochondrial DNA haplogroups - de Saint Pierre, Michelle (2012)
After several years of research, there is now a consensus that America was populated from Asia through Beringia, probably at the end of the Pleistocene. But many details such as the timing, route(s), and origin of the first settlers remain uncertain. In the last decade genetic evidence has taken on a major role in elucidating the peopling of the Americas. To study the early peopling of South America, we sequenced the control region of mitochondrial DNA from 300 individuals belonging to indigenous populations of Chile and Argentina, and also obtained seven complete mitochondrial DNA sequences. We identified two novel mtDNA monophyletic clades, preliminarily designated B2l and C1b13, which together with the recently described D1g sub-haplogroup have locally high frequencies and are basically restricted to populations from the extreme south of South America. The estimated ages of D1g and B2l, about ∼ 15,000 years BP, together with their similar population dynamics and the high haplotype diversity shown by the networks, suggests that they probably appeared soon after the arrival of the first settlers and agrees with the dating of the earliest archaeological sites in South America (Monte Verde, Chile, 14,500 BP). One further sub-haplogroup, D4h3a5, appears to be restricted to Fuegian-Patagonian populations and reinforces our hypothesis of the continuity of the current Patagonian populations with the initial founders. Our results indicate that the extant native populations inhabiting South Chile and Argentina are a group which had a common origin, and suggest a population break between the extreme south of South America and the more northern part of the continent. Thus the early colonization process was not just an expansion from north to south, but also included movements across the Andes.